Admission D-dimer levels, D-dimer trends, and outcomes in COVID-19. Issue 196 (December 2020) - Naymagon, Leonard; Zubizarreta, Nicole; Feld, Jonathan; van Gerwen, Maaike; Alsen, Mathilda; Thibaud, Santiago; Kessler, Alaina; Venugopal, Sangeetha; Makki, Iman; Qin, Qian; Dharmapuri, Sirish; Jun, Tomi; et al.
Abstract: Observational data suggest an acquired prothrombotic state may contribute to the pathophysiology of COVID-19. These data include elevated D-dimers observed among many COVID-19 patients. We present a retrospective analysis of admission D-dimer, and D-dimer trends, among 1065 adult hospitalized COVID-19 patients, across 6 New York Hospitals. The primary outcome was all-cause mortality. Secondary outcomes were intubation and venous thromboembolism (VTE). Three-hundred-thirteen patients (29.4%) died, 319 (30.0%) required intubation, and 30 (2.8%) had diagnosed VTE. Using Cox proportional-hazard modeling, each 1 μg/ml increase in admission D-dimer level was associated with a hazard ratio (HR) of 1.06 (95%CI 1.04–1.08, p < 0.0001) for death, 1.08 (95%CI 1.06–1.10, p < 0.0001) for intubation, and 1.08 (95%CI 1.03–1.13, p = 0.0087) for VTE. Time-dependent receiver-operator-curves for admission D-dimer as a predictor of death, intubation, and VTE yielded areas-under-the-curve of 0.694, 0.621, and 0.565 respectively. Joint-latent-class-modeling identified distinct groups of patients with respect to D-dimer trend. Patients with stable D-dimer trajectories had HRs of 0.29 (95%CI 0.17–0.49, p < 0.0001) and 0.22 (95%CI 0.10–0.45, p = 0.0001) relative to those with increasing D-dimer trajectories, for the outcomes death and intubation respectively. Patients with low-increasing D-dimer trajectories had a multivariable HR for VTE of 0.18 (95%CI 0.05–0.68, p = 0.0117) relative to those with high-decreasing D-dimer trajectories. Time-dependent receiver-operator-curves for D-dimer trend as a predictor of death, intubation, and VTE yielded areas-under-the-curve of 0.678, 0.699, and 0.722 respectively. Although admission D-dimer levels, and D-dimer trends, are associated with outcomes in COVID-19, they have limited performance characteristics as prognostic tests. Highlights: We present a retrospective analysis of admission D-dimer, and D-dimer trends, among adults hospitalized for COVID-19. 1065 inpatients from 6 hospitals were included; outcomes included mortality, intubation, and VTE. Admission D-dimers and D-dimer trends were associated with outcomes in COVID-19. However, D-dimer levels and trends were limited prognostic tests in COVID-19. The role of D-dimer levels in COVID-19 clinical decision making remains unclear.